2018
DOI: 10.1002/er.4061
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of a passive core cooling design for cylindrical lithium-ion batteries

Abstract: Summary Battery thermal management (BTM) system is an indispensable component for large‐sized lithium‐ion battery packs used in aerospace and automotive applications. Besides providing a proper temperature range for batteries to operate, thus improving their efficiency, lifespan, and safety, the BTM system also needs to be well designed with considering the cost, weight, and practicability. In this paper, an internal passive BTM system is proposed for the cylindrical Li‐ion batteries. The design embeds a phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 37 publications
(59 reference statements)
0
27
0
Order By: Relevance
“…They found a significant temperature difference of 45°C when comparing CPCM cooling and air convective cooling. Zhao et al embedded a mandrel which contains PCM into a battery unit to provide passive cooling. A developed cell was tested under different scenarios and provided validation to the numerical modelling.…”
Section: Introductionmentioning
confidence: 99%
“…They found a significant temperature difference of 45°C when comparing CPCM cooling and air convective cooling. Zhao et al embedded a mandrel which contains PCM into a battery unit to provide passive cooling. A developed cell was tested under different scenarios and provided validation to the numerical modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal and charging safety have been extensively studied in the literature . Cylindrical, prismatic, and pouch LIBs are the main types of LIBs used in EVs.…”
Section: Introductionmentioning
confidence: 99%
“…FM Global carried out the combustion experiments of large capacity LIB pack and found that the combustion behavior of LIB pack was different from a single cell . In addition, numerous efforts have been devoted to design more efficient and advanced battery thermal management (BTM) systems to prevent thermal runaway propagation, including phase change material (PCM) cooling, air cooling, cooling plates, and heat pipe cooling . Fire behaviors under aviation environment is different from normal conditions, which is determined by the environmental pressure.…”
Section: Introductionmentioning
confidence: 99%